Pengembangan Aplikasi Profil Dasbor Terhadap Pelanggan Optik Opticalgo Berbasis Android - Dionisius Wisnu Indarto; Paramaresthi Windriyani (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The study aims to develop a dashboard profile app for Opticalgo customers, which runs on smartphones with the Android operating system. This dashboard profile application can be used for Opticalgo-specific customers who have done eye checks through opticalgo offline stores or other people who want to make glasses purchases through the Opticalgo application. The development method used is Rational Unified Process (RUP), and its modeling is Unified Modelling Language (UML). The application development used is Visual Studio Code as an IDE code editor with react native programming languages, java, and javascript for modeling application creation on the admin dashboard website. The results obtained in this study are that the application is expected to run on an Android-based system to get historical information for customers related to prescriptions, transactions, points, profits owned after doing activities in opticalgo offline and online stores and making glasses purchases based on the category of glasses selected in Opticalgo application.